2005
DOI: 10.1017/s0001924000000841
|View full text |Cite
|
Sign up to set email alerts
|

Air Travel – Greener by Design Mitigating the environmental impact of aviation: Opportunities and priorities

Abstract: The Technology Sub-Group of Air Travel – Greener by Design was instituted at the first full meeting of the GBD community in March 2000. Its first period of intense activity was from the summer of 2000 to the spring of 2001, culminating in the publication of its report The Technology Challenge in July 2001 at the first Air Travel – Greener by Design Conference at the Royal Aeronautical Society. In the period that followed, the contents of the report were further disseminated by presentations at conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…I, the engine design can have a strong effect on the emitted species. Although high pressure ratios and temperatures typically lead to reduced fuel consumption, and thus low(er) CO 2 emissions, they also increase the production of thermal NO x [16]. The production of NO x is also influenced by the detailed combustor design, which is not captured by the current design vector and is out of scope for the current study.…”
Section: Propulsionmentioning
confidence: 97%
See 1 more Smart Citation
“…I, the engine design can have a strong effect on the emitted species. Although high pressure ratios and temperatures typically lead to reduced fuel consumption, and thus low(er) CO 2 emissions, they also increase the production of thermal NO x [16]. The production of NO x is also influenced by the detailed combustor design, which is not captured by the current design vector and is out of scope for the current study.…”
Section: Propulsionmentioning
confidence: 97%
“…Although it was shown that such engine cycle modifications can yield a significant reduction in fuel burn (33 to 45% for a large single-aisle aircraft), they may have an adverse effect on non-CO 2 climate effects. Raising the OPR and TET, for example, increases the formation of thermal NO x [16], although the emission index of NO x in LTO and cruise can be further reduced through future combustor technologies [17]. Additionally, increasing the bypass ratio of turbofan engines increases the probability of contrail formation [18].…”
mentioning
confidence: 99%
“…As briefly introduced in Section I, the engine design can have a strong effect on the emitted species. While high pressure ratios and temperatures typically lead to reduced fuel consumption and thus low(er) CO 2 emissions, they also increase the production of thermal NO x [14]. The production of NO x is also influenced by the detailed combustor design, which is not captured by the current design vector and is out of scope for the current study.…”
Section: Propulsionmentioning
confidence: 97%
“…Although in recent years the bypass ratio (BPR), OPR and TET have been increased to decrease the specific fuel consumption, this may have an adverse effect on climate impact. Raising the OPR and TET, for example, increases the formation of thermal NO x [14], while increasing the bypass ratio of turbofan engines increases the probability of contrail formation [15]. This demonstrates that optimizing for minimum fuel burn, again, does not necessarily align with the objective of minimizing global-warming impact.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical implementation point of view, it can be observed that the variation of aircraft/airport operational procedures emerges as a suitable option that can result in short term improvements and could be less costly in comparison with the other options. For this approach, the optimal design of routes for departures and arrivals, and the allocation of aircraft to these routes are considered as the most promising options (Green, 2005).…”
Section: Introductionmentioning
confidence: 99%